2022
DOI: 10.20517/cdr.2021.112
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to identifying drug resistance mechanisms to clinically relevant treatments in childhood rhabdomyosarcoma

Abstract: Aim: Despite aggressive multiagent protocols, patients with metastatic rhabdomyosarcoma (RMS) have poor prognosis. In a recent high-risk trial (ARST0431), 25% of patients failed within the first year, while on therapy and 80% had tumor progression within 24 months. However, the mechanisms for tumor resistance are essentially unknown. Here we explore the use of preclinical models to develop resistance to complex chemotherapy regimens used in ARST0431. Methods: A Single Mouse Testing (SMT) protocol was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Although mixed aRMS/eRMS patient phenotypes are clinically possible (56,57), preclinical studies in our sample used aRMS and eRMS separately. Ghilu et al assessed drug sensitivity and resistance in different aRMS and eRMS CDX and PDX models using Single Mouse Testing protocol (58). Another example is the study conducted by Stewart et al, utilizing the orthotopic PDX model of both aRMS and eRMS to test therapeutic targets for RMS through genomic, epigenomic, and proteomic analyses (59).…”
Section: From Bedside To Benchmentioning
confidence: 99%
“…Although mixed aRMS/eRMS patient phenotypes are clinically possible (56,57), preclinical studies in our sample used aRMS and eRMS separately. Ghilu et al assessed drug sensitivity and resistance in different aRMS and eRMS CDX and PDX models using Single Mouse Testing protocol (58). Another example is the study conducted by Stewart et al, utilizing the orthotopic PDX model of both aRMS and eRMS to test therapeutic targets for RMS through genomic, epigenomic, and proteomic analyses (59).…”
Section: From Bedside To Benchmentioning
confidence: 99%
“…Conventional chemotherapy generally involves using the maximum tolerated dose (MTD) to kill as many tumor cells as possible and administering it every 2-4 weeks with a long drug-free break to enable patients to recover from the residual effects of chemotherapy [1,2]. Despite this strategy being supported by a high response rate of disease regression or stabilization, it seems to be less effective over the long term due to MTD-related toxicity, drug resistance, and even tumor progression [3,4]. About 20 years ago, preclinical studies demonstrated that cytotoxic drugs, given in short intervals at low doses and without interruption, could induce tumor regression by targeting tumor vascular endothelial cells [5][6][7].…”
Section: Introductionmentioning
confidence: 99%